In vitro evaluation of neutral oximes as reactivators of parathion-inhibited electric eel acetylcholinesterase - Lima, Joselia A.; Cavalcanti, Laura P.A.N.; Aguiar, Alcino P.; Rezende, Claudia M.; Lima, Keila S.C.; Lima, Antonio L.S. (Defence Life Science Journal, 2017)
Organophosphorus (OP) compounds are irreversible inhibitors of acetylcholinesterase (AChE) commonly used as pesticides and, unfortunately, as nerve agents in terrorist attacks. These compounds are highly soluble easily crossing the blood-brain barrier (BBB). Clinically, oximes such as pralidoxime and obidoxime are used for the reactivation of AChE. These oximes are not sufficiently effective to reactivate AChE inhibited by different OPs besides the fact that they are permanently charged and do not readily cross the BBB. This work evaluated the ability of ten neutral oximes to reactivate parathion-inhibited eel AChE. Because oximes can bind to AChE as reversible inhibitors, this property was also evaluated, with pralidoxime (2-PAM) used as a reference compound. Unlike 2-PAM, which inhibited AChE in a concentration-dependent manner, neutral oximes were not good inhibitors of AChE. Neutral ligands can present affinity for the PAS site. Neutral oximes 1 and 2 (200 mM) reactivated parathion-inhibited eel AChE by 9% and 11%, respectively; but neither of them surpassed the reactivation efficacy of 2-PAM (25%). Neutral oximes 1 and 2 reactivated AChE at a safe concentration for humans. Both neutral oximes 1 and 2 are good non-quaternary moieties for the synthesis of conjugates with enhanced reactivation potency and BBB penetration.